Clinical validation study of the SignCare Vital Signs Monitor of Fundación Cardiovascular de Colombia (2016)
Introduction: In Colombia, due to the difficult access to health services and to geographic conditions, the implementation and innovation of telemedicine technological tools is a priority. Having a validated vital signs monitor (VSM) improves proper medical treatment and diagnosis.Objective: To design and perform clinical trials for the SignCare VSM.Materials and methods: A device for continuous monitoring of electrocardiography, respiration, oxygen saturation, temperature and noninvasive blood pressure (NIBP) was designed. This device was validated in a laboratory in order to ensure a robust prototype, close to the level of commercial medical devices. Clinical trials were performed through a cross-section study with 98 patients, whose vital signs were measured using the SignCare monitor and a commercial monitor. These two measurements were compared using Pearson’s correlation coefficients.Results: There were no statistically significant differences between the results obtained with the SignCare VSM and the commercial monitor. The highest correlations were found for the following items: heart rate by electrocardiogram (r=0.844), heart rate by oxymetry (r=0.821), body temperature (r=0.895), systolic blood pressure (r=0.780), and diastolic blood pressure (r=0.811).Conclusions: The SignCare device is as reliable as the commercial monitor in the qualitative detection of morphologic alterations of electrocardiogram records, as well as in breathing, temperature, oxygen saturation and blood pressure parameters, which makes it recommendable for clinical use in adult population.